The role of geographic information systems in analyzing the geospatial distribution of private education institutions in the municipal branch of Misrata (مجلة جامعة سرت للعلوم الانسانية, 2024)
The study aims to identify the reality of the geospatial distribution of private education institutions in the central municipal branch of Misrata, and to identify the extent of variation in distribution, using Geographic Information Systems (GIS), the most important modern geographic techniques that geographers have relied on in studying the spatial analysis of point geographic phenomena, such as educational institutions that have their own standards. Planning, determining their patterns of spread and revealing their spatial relationships through the tools they possess capable of spatial statistical analysis of geographical phenomena. The study concluded that the distributional trend of these institutions takes an oval shape with a longitudinal direction concentrated in the north and northwest of the municipal branch, where it reached The value of the deviation is (16.28) degrees, and the value of the standard score for private education institutions in the municipal branch of Misrata in 2023 reached (795.6) at the confidence level (0.05) and outside the critical value (1.96 - 2.58), while the nearest neighbor comparison reached (96.41), which indicates Uniformly divergent distribution pattern.
Keywords: special education; geospatial analysis; planning standards; neighborhood connection; allocation areas